Application of Snowball Throwing Model to Improve Students’ Understanding of Concepts and Communication Skills in Gas Kinetic Theory - Siti Nurlina Ripani; Yanti Sofi Makiyah (Berkala Ilmiah Pendidikan Fisika, 2021)
This research is based on the number of students who find it difficult to learn physics because of the lack of understanding of concepts and only memorization and still lack of communication skills of students. Based on this background, a study was conducted that aims to improve the understanding of students' concepts and communication skills by applying snowball throwing learning model on gas kinetic theory material. The method used in this study is experimental method, the population in this study is all students of XI IPA SMA IT Nurul Jannah and then selected with simple random sampling technique so that there are 23 students of grade XI IPA SMA IT Nurul Jannah. The result of the study is the application of snowball throwing model can improve the understanding of the concept with a pretest average of 25,6 and then increase by a posttest average of 57,4, with a large N-gain of 0,4 so that the medium category and t-test results of 7,65 are greater than the table t with a confidence level of 5%. The snowball throwing learning model can also improve students' communication skills, with an initial average of 45,41 and after the application of the model to 67,15, with a large N-gain of 0,4 so that the medium category, as well as the t-test results are 8,48 greater than the large, t-table that is 2,07. So, it can be concluded that the Learning Model of Snowball Throwing can improve the concept and communication skills understanding of student. For further research, it is recommended to utilize learning media to improve concept understanding by collaborating using snowball throwing learning models.